"EU FALO, EU MINTO": A EXPERIÊNCIA NO ESPAÇO LITERÁRIO EM O FALSO MENTIROSO, DE SILVIANO SANTIAGO - Silva, Mayara Bueno da (2016)
This study aims the reading of the novel O falso mentiroso: memórias, by Silviano Santiago, as literary space, according to Maurice Blanchot‘s concept, where literary experiences enable an action of dilution of its own limits, such as reality and fiction, in a constant self-questioning exercise. The axis of Silviano Santiago‘s critical thought axis is the ―space-in-between" concept, based on the anthropophagic ritual, which deconstructs binary speeches and the concept of origin. Essential to us understand the literary relations and how this studied novel sets dialogs between fiction and the author‘s theory, therefore, between the fictitious writer and the reviewer. Connected to discussions of authors such as Walter Benjamin, Michael Foucault e Giorgio Agamben, we conceive Silviano Santiago‘s novel literary space as a place of deconstruction, where statutes are rated under suspicion and where the literature is also, theory.